Going Local: How Coastal Environmental Settings Can Help Improve Global Mangrove Carbon Storage and Flux Estimates. Issue 22 (23rd November 2022) - Taillardat, Pierre
Abstract: The magnitude and variability of mangrove carbon storage are uncertain and still being discussed. In a recent article, Breithaupt and Steinmuller (2022, https://doi.org/10.1029/2022GL100177 ) completed a literature review and compared mangrove organic carbon burial rates between different coastal environmental settings (CES) that integrate sedimentary supply (terrigenous vs. carbonate) and hydrogeomorphic settings (delta, estuary, lagoon, open coast). They found greater burial rates in terrigenous delta and estuaries while lower rates were reported in lagoons and carbonate settings. Surprisingly, these CES relationships do not strictly match previous mangrove soil carbon stock estimates but were consistent with biomass stocks. The CES approach used by Breithaupt and Steinmuller should be used for other mangrove carbon stocks and fluxes estimates to refine our understanding of mangrove carbon cycling and storage. Plain Language Summary: Mangrove forests are intertidal ecosystems efficient at trapping carbon in their sediments. While this ecological process is well recognized, the quantity of carbon being deposited is still uncertain. Considering the growing number of studies that have collected samples to estimate carbon burial rates, Breithaupt and Steinmuller (2022, https://doi.org/10.1029/2022GL100177 ) recently published a meta‐analysis to compile and compare carbon burial between mangrove types. Their study reported great variability between mangrove types based on their sediment supply and geomorphological configuration. Their results are interesting because they go against previous estimates of mangrove carbon stocks distribution. Also, the approach used has the potential to be applied to other components of the mangrove carbon budget. Doing so would improve our fundamental understanding of carbon cycling in mangrove ecosystems. It would also help refine carbon storage estimates for future conservation projects interested in generating carbon credits. Key Points: Carbon burial rates between mangrove sedimentary and geomorphic types were analyzed in Breithaupt and Steinmuller (2022, https://doi.org/10.1029/2022GL100177 ) Greater carbon burial rates were reported in terrigenous deltas and estuaries rather than in lagoons and carbonate settings Comparing carbon burial rates with other stocks and fluxes between mangrove types can help refine the global mangrove carbon budget